2019
DOI: 10.1002/ps.5424
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the potential distribution of arbovirus vector Aedes aegypti under current and future climate scenarios in Taiwan, China

Abstract: BACKGROUND: Aedes aegypti is one of the most important mosquito species and is a common disease-transmitting pest in tropical areas. Various infectious arbovirus diseases can be transmitted by Ae. aegypti. With ongoing global climate change, we are facing an increasing public health threat from the rapid spread of disease vectors into wider geographical areas. To better understand the current ecological niche range and possible future expansion of Ae. aegypti, an ecological niche modelling approach was adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 49 publications
(51 reference statements)
1
22
0
2
Order By: Relevance
“…In this compiled data set of 12 977 occurrence records, many duplicates and occurrences in close proximity were identified and removed for subsequent analysis to avoid spatial autocorrelation ( cf . Liu et al …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this compiled data set of 12 977 occurrence records, many duplicates and occurrences in close proximity were identified and removed for subsequent analysis to avoid spatial autocorrelation ( cf . Liu et al …”
Section: Methodsmentioning
confidence: 99%
“…In this compiled data set of 12 977 occurrence records, many duplicates and occurrences in close proximity were identified and removed for subsequent analysis to avoid spatial autocorrelation (cf . Liu et al 40 ). We considered only one occurrence record per grid cell (spatial resolution of 5 arcmin as for climatic conditions, see below) even if more than one occurrence was recorded, resulting in 7406 grid cells, i.e.…”
Section: Occurrence Datamentioning
confidence: 99%
“…[18][19][20][21] Despite the diversity of strategies available to control the vector population, the incidence of arboviruses has increased and correlated with climate changes that favor the mosquitoes proliferation in new areas. 22 One of the chemical control alternatives that has been proposed is the use of products capable of killing Ae. aegypti larvae.…”
Section: Introductionmentioning
confidence: 99%
“…aegypti related to dengue fever incidence in Africa. Previous studies demonstrated that climate changes have increased the burden of many vector-borne diseases [18,31,33,34]. Studies indicating that the risk of dengue fever incidence is expected to increase globally under future climate change predictions [6,31,35].…”
Section: Discussionmentioning
confidence: 99%